Formalistic analysis of pewter design based on Islamic ornamentation art / Siti Mastura Md Ishak and Nor Azlin Hamidon - Md Ishak, Siti Mastura; Hamidon, Nor Azlin (Faculty of Art and Design, 2024)
Design elements are influenced by the diversity of the designer's thinking context such as style and technical results, design concepts and aesthetic values. This reasonableness is also able to make local pewter products a potential medium to highlight the skills of Malay designers in conveying the meaning and significance of each design product that has a psychological characteristic. However, the design needs to be articulated without carelessness so that its aesthetic value is able to increase an art product precisely from the point of view of meaning. This study aims to analyse pewter designs that have an atmosphere of Malay culture and thought in Malaysia based on the theoretical innovation of Islamic ornamentation art. Observation of artefacts is used to support the formalistic analysis process on design structure and motifs with visual documentation of artefacts to describe the details of the ornamentation structure. The analysis is carried out based on two Islamic and Malay theories to obtain the results of the formation of designs and understand the innovation of thinking that occurs. The results of this study found parallelism in the integration of both types of art concepts that are able to have a meaningful impact on the generation of pewter design ideas. This study is seen as a step to dignify the theory of local art in Islamic values that can be a guide in the empowerment of Malay designers at the global level.